Governmentality, rights and EU legal scholarship: a Foucauldian analysis - Sokhi-Bulley, Bal (2009)
The Fundamental Rights Agency (FRA) of the European Union came into being on 1 March 2007 and represents a new institution for human rights protection in the EU. This thesis undertakes a critical analysis of the FRA from a governmentality perspective. Governmentality refers to a particular critical standpoint, inspired by the work of Michel Foucault, which is concerned with power relations as processes of government. The features of the FRA, its structure and functions, are framed using "governance talk". The particular features which this thesis is interested in analysing are: the multiplicity of actors which make up the network structure of the Agency, their classification as experts, and the collection of information and data as statistics. The thesis demonstrates that these features, conceptualised as governance in institutional discourse, are actually features of governmentality. I therefore suggest that the rights discourse of the FRA is a discourse of governmentality. Moreover, I show how governmentality necessarily involves self-government: the actors and experts in the FRA's rights discourse govern themselves. This has significant implications for rights discourse: it reveals processes of governing (through) rights. On the one hand, we witness processes of the government of rights through experts and statistics. On the other, we are alerted to government in the name of rights. The thesis therefore intervenes within the EU's rights and governance discourses: it exposes the relations of power (as governmentality) that conventional "governance talk" tries to hide. It highlights the elusive novelty of theorising, and of critique, in EU legal scholarship on rights. By presenting a new perspective on the rights discourse of the FRA using governmentality, this thesis seeks to contribute to EU legal scholarship on rights, filling a glaring and significant gap in the literature.